Use of rocky intertidal pools by shrimp species in a temperate area - Vinagre, Catarina (2020)
Rocky shores are among the most-intensively studied ecosystems, however, tidal pools remain relatively understudied. This study aims to investigate the habitat use and dynamics of the shrimp species that occur in tidal pools of a North-eastern Atlantic coast, the Portuguese coast, in particular species composition, abundance, seasonality and size structure. Shrimps were sampled monthly from six tidal pools for one year, in the west Portuguese coast. Species diversity was much higher than that found in previous studies, in other parts of the world. The shrimp population comprised 8 species: the European rock shrimp, Palaemon elegans, the common prawn, Palaemon serratus, the Atlantic ditch shrimp, Palaemon varians, the Baltic prawn, Palaemon adspersus, the Oriental shrimp, Palaemon macrodactylus and the relatively rare shrimps Eualus sollaudi, Eualus drachi and Caridion gordoni. Shrimp populations varied seasonally and among pools, with peak numbers in spring and summer. The most abundant species was P. elegans. P. elegans was present in all pools, throughout most of the year. Rare and exotic species were present mostly in spring-summer. Lower mean sizes of all shrimp were registered in the beginning of spring, most often in April or May, and gradually increased until winter. New-recruits of the most abundant species, P. elegans, generally entered the pools in spring and formed a high proportion of the population between April and August. They were responsible for the highest abundance peaks of shrimps occurring in the pools. The species richness and high numbers of juveniles occurring in tidal pools suggest that these environments may be nursery areas for coastal shrimp.